Forsythiasides-Rich Extract From Forsythiae Fructus Inhibits Mast Cell Degranulation by Enhancing Mitochondrial Ca2+ Uptake - Qi, Ruijuan; Kang, Yuan; Li, Ximeng; Zhang, Xiaoyu; Han, Yixin; Cai, Runlan; Gao, Yuan; Qi, Yun (Frontiers in Pharmacology, 2021)
Mast cells (MCs) activated via IgE/FcεRI or MAS-related G protein coupled receptor (Mrgpr)-mediated pathway can release granules that play prominent roles in hypersensitivity reactions. Forsythiae Fructus, a well-known traditional Chinese medicine, has been clinically used for allergic diseases. Although previous studies indicated that Forsythiae Fructus extract inhibited compound 48/80-induced histamine release from MCs, its effect on IgE-dependent MC degranulation and possible underlying mechanisms remain to be explored. Herein, we prepared the forsythiasides-rich extract (FRE) and investigated its action on MC degranulation and explored its underlying mechanism. Our data showed that FRE could dampen IgE/FcεRI- and Mrgpr-mediated MC degranulation in vitro and in vivo. Mechanistic study indicated that FRE decreased cytosolic Ca2+ (Ca2+[c]) level rapidly and reversibly. Moreover, FRE decreased Ca2+[c] of MCs independent of plasma membrane Ca2+-ATPase (PMCA), sarco/endoplasmic Ca2+-ATPase (SERCA) and Na+/Ca2+ exchanger (NCX). While, along with Ca2+[c] decrease, the increase of Ca2+[m] occurred simultaneously in FRE-treated RBL-2H3 cells. In the isolated mitochondria, FRE also promoted the subcellular organelle to uptake more extramitochondrial Ca2+. In conclusion, by increasing Ca2+[m] uptake, FRE decreases Ca2+[c] level to suppress MC degranulation. Our findings may provide theoretical support for the clinical practice of Forsythiae Fructus on allergy treatment and in other MC-involved diseases.